PELIBATAN MASYARAKAT LOKAL DALAM PENYEDIAAN PENGINAPAN LOKAL (HOMESTAY) DI DESA WISATA TISTA, KABUPATEN TABANAN - Agung Sri Sulistyawati; Ida Ayu Trisna Eka Putri; Fanny Maharani Suarka; Putu Ratih Pertiwi (Buletin Udayana Mengabdi, 2018)
Tista Tourism Village is the developing tourist village, that located at Kerambitan Village, Tabanan Regency. The purpose of this community service is to deliver the understanding and skills, improving for Tista community in playing an active role and participation in preparation of local lodging (homestay) along with supporting facilities to provide security and comfort when tourists stay and can increase tourists length of stay at Tista Tourism Village to enjoy various tourism products and tour packages in Tista Village in support of development and management of Tista Tourism Village, so as to provide economic benefits in directly to the Tista Village community. The devotion technique that is giving counseling to the tista village community which was attended by the village head, the chairman of pokdarwis, the manager of the tourist village and the community, the subject that presented about the homestay to be clean, confortable, and the availability of clean water. Homestay is prepared to be the main accommodation alternative for tourists whotakes the vacation at Tista Wisata Village. But about the cleanliness, is still a shortcoming that must be addressed. Not only homestay, a number of tourist destinations that are intended to attract tourists, should provide the widest information to tourists and maintain the cleanliness of the surrounding environment. All parties must be involved in fixing the existing shortcomings, because to increase tourism requires a high awareness, ie the community will be involved.